THE STRUCTURAL AND MAGNETIC PROPERTIES OF La1-xCaxMnO3WITH x = 0.27 AND 0.47. - Y. E. Gunanto; B. Kurniawan; S. Poertadji; A. A. Wisnu; A. Purwanto; H. Tanaka; T. Ono (Jurnal Sains Materi Indonesia, 2012)
THE STRUCTURAL AND MAGNETIC PROPERTIES OF La1-xCaxMnO3WITH x = 0.27 AND 0.47. We have studied the structural and magnetic properties for La1-xCaxMnO3 with x = 0.27 and 0.47 using neutron powder diffraction and magnetization measurements. At room and low temperature, all samples have the orthorhombic structure with space group Pnma. The sample x = 0.47 shows the antiferromagnetic mix a ferromagnetic with the magnetic moment and the Curie temperature are 1.30 μB and 260K, respectivelywhile the sample x = 0.27 is a ferromagnetic with the magnetic momentand the Curie temperature are 3.10 μB  and 197K, respectively.